The Used of Benime Application For Mufradat - Fitri Hanifah; A-eshah Emil Waemah; Abdullah Wahud bin Salleh (Yayasan Adra Karima Hubbi, 2022)
The development of technology in the world of Arabic language education has become a necessity. The COVID-19 pandemic has changed the learning process, including learning Arabic. In this study, the bemine application in class X in Man 1 Padang Panjang really helped the teaching and learning process of students, where students could understand learning by means of the power point presentation method, games performed by educators, as well as the exercises given each year. Days by educators to support the Arabic learning process. This research is a qualitative research, quality research is an Arabic language study using a collection of journals or e-books. The purpose of this study is to describe the benefits and uses of the Benime application for mufradat learning. With this research, we can utilize and apply learning media, which previously did not understand technology, finally we can use and try it, And educators can take advantage of advanced applications or media to support achievement or the learning process in our country, because improving the quality of education must be considered by way of Provides the best way to be able to network communication with everyone, so this Benime application is very helpful and useful in learning maharah qiraah or mufradat At Madrasah Aliyah Negeri 1 Padang Panjang.